Peran Museum Linggarjati sebagai Destinasi Wisata Sejarah dan Budaya dalam Konteks Pendidikan Sejarah - Sopian Sopian; Shanti Hekmawati; Erna Mustika Rini; Tia Siti Atikah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Linggarjati Museum is a historical site with significant importance in Indonesia’s diplomatic journey during the independence revolution, particularly in relation to the Linggarjati Agreement of 1946. This study aims to analyze the role of the Linggarjati Museum as a historical and cultural tourism destination and its relevance in strengthening history education. This research uses a descriptive qualitative approach through literature studies and document analysis related to museum functions, the concept of historical tourism, and character education based on national values. The results of the study indicate that the Linggarjati Museum not only functions as an institution for preserving artifacts and the nation’s collective memory, but also as a contextual learning resource capable of improving students’ understanding of the dynamics of Indonesia’s independence diplomacy. The integration of museum visits into the history learning process contributes to improving historical literacy, historical awareness, and the internalization of nationalism and diplomacy values. In addition, museum management based on educational tourism and sustainability principles has the potential to strengthen local cultural identity while supporting the development of the regional tourism sector. Thus, the Linggarjati Museum has a strategic role as a living history laboratory that is relevant to strengthening the quality of history education in Indonesia.